Insights on biorational potential of Ocimum gratissimum essential oil and its binary combination with monoterpene phenol for control of rice weevil (Sitophilus oryzae) and aflatoxigenic fungi. - Remesh, V. Archana; Raveendran, Ashika; Bincy, K.; Wagh, Vasudev S.; Dastager, Syed G.; Babu, C. S. Vivek (Food Bioscience, 2022)
Food grain storage is a difficult task due to insect infestation and subsequent mycotoxin contaminations which adversely affects the nutritional quality of grains and leading to economic loss. Current research focuses on contact and fumigant toxicity effects of essential oils (EO) and aroma compounds against Sitophilus oryzae and growth inhibition of aflatoxigenic fungi. The EO of Ocimum gratissimum comprised of thymol (46.8%), gamma-terpi-nene (14.04%) along with o-cymene (11.76%). Also, Cymbopogon flexuosus rich in citral (76.3%) and geraniol (84.6%) and Cymbopogon nardus having geraniol (49.24%) and geranyl acetate (20.9%) were all evaluated using a dose of 25 mu L (Conc-833.3 mu L/L air) against S. oryzae. All the compounds showed significant mortality (>95%) at 24 h of exposure. The insecticidal property of O. gratissimum oil chemotype showed a strong contact and fumigant toxicity against S. oryzae at a highest dose of 25 mu L (Conc-833.3 mu L/L air) within 24 h. It has been further evaluated on three aflatoxigenic fungal strains which showed reduction in growth and aflatoxin content (Aflatoxin B and G), which was markedly reduced upon the treatment. The binary mixture interaction of O. gratissimum oil with monoterpene phenol (carvacrol) was assessed and the specific binary mixture of 80:20 ratio (having additive property) acts as a contact insecticide with 100% mortality. Hence, essential oil of less explored Ocimum species (O. gratissimum) and its binary mixture could be deployed as potential biorational for control of rice weevil (Sitophilus oryzae) and aflatoxigenic Aspergillus spp.
Keywords: Aflatoxigenic fungi; Binary combination; Essential oil; Ocimum gratissimum; Sitophilus oryzae

Isolation and structural characterization of exopolysaccharide from marine Bacillus sp. and its optimization by Microbioreactor - Wagh, Vasudev S.; Said, Madhukar S.; Bennale, Jagadish S.; Dastager, Syed G. (Carbohydrate Polymers, 2022)
In the present study, a cost-effective, robust Microbioreactor based production optimization of levan like exopolysaccharide from marine Bacillus sp. SGD-03 was analysed. FE-SEM analysis has showed the significant fibrillar structure of EPS. Size exclusion chromatography and other analytical data revealed that, produced EPS has a molecular weight of 1.0 x 10(4) Da and is composed of fructose monosaccharide with hydroxyl, carbonyl, and ether groups. The backbone structure of EPS has a branching pattern of beta-(2,6) linkages which confirms the similarity with available levan like polymers. The cost-effective media composition for levan production was demonstrated. The maximum yield of crude levan obtained was 123.9 g/L by response surface methodology using robust BioLector Pro Microbioreactor, and same has been validated with shake flask, 1 L and 10 L pilot-scale fermentation.
Keywords: EPS; marine; Microbioreactor; Optimization; structure